Exploring the microstructure of hydrated collagen hydrogels under scanning electron microscopy. (13th February 2023) - Merryweather, Daniel J.; Weston, Nicola; Roe, Jordan; Parmenter, Christopher; Lewis, Mark P.; Roach, Paul
Abstract: Collagen hydrogels are a rapidly expanding platform in bioengineering and soft materials engineering for novel applications focused on medical therapeutics, medical devices and biosensors. Observations linking microstructure to material properties and function enables rational design strategies to control this space. Visualisation of the microscale organisation of these soft hydrated materials presents unique technical challenges due to the relationship between hydration and the molecular organisation of a collagen gel. Scanning electron microscopy is a robust tool widely employed to visualise and explore materials on the microscale. However, investigation of collagen gel microstructure is difficult without imparting structural changes during preparation and/or observation. Electrons are poorly propagated within liquid‐phase materials, limiting the ability of electron microscopy to interrogate hydrated gels. Sample preparation techniques to remove water induce artefactual changes in material microstructure particularly in complex materials such as collagen, highlighting a critical need to develop robust material handling protocols for the imaging of collagen hydrogels. Here a collagen hydrogel is fabricated, and the gel state explored under high‐vacuum (10 −6 Pa) and low‐vacuum (80–120 Pa) conditions, and in an environmental SEM chamber. Visualisation of collagen fibres is found to be dependent on the degree of sample hydration, with higher imaging chamber pressures and humidity resulting in decreased feature fidelity. Reduction of imaging chamber pressure is used to induce evaporation of gel water content, revealing collagen fibres of significantly larger diameter than observed in samples dehydrated prior to imaging. Rapid freezing and cryogenic handling of the gel material is found to retain a porous 3D structure following sublimation of the gel water content. Comparative analysis of collagen hydrogel materials demonstrates the care needed when preparing hydrogel samples for electron microscopy. Lay Description: In order to support the development of engineered living tissues, materials scientists and biologists have been making use of soft, porous materials that have a high proportion of water within their structure similar to environments found within the body. These can be used for the delivery of cells for medical therapies or used within the laboratory to grow artificial tissues as models, along with other applications. One of the main factors affecting the performance of these water‐filled gels (hydrogels) is the physical structure at the micro‐scale (roughly one tenth the thickness of a human hair). Visualisation of these structures is difficult, with many methods requiring water to be removed prior to analysis. However, by removing or freezing the water contained within, small structural features are put under immense stress and often suffer damage, such that the structure observed is not what would normally be presented to living cells in normal circumstances. New technologies enable different ways of measuring and assessing samples. Here we present the visualisation of collagen hydrogels using a number of methods where their original structures are retained. Here a collagen hydrogel is analysed using scanning electron microscopy methods in different ways: under vacuum where water is removed, under low pressure, and normal atmospheric pressure, with water retained and visualised with the collagen. We show the native structures formed in these collagen hydrogels and how they are altered upon visualisation under the different imaging conditions. These results are useful to a broad audience, particularly those working on medical related materials, who may not fully appreciate the structures observed in normal hydrated conditions.